ZnII-2,2?:6?,2?-terpyridine-based complex as fluorescent chemosensor for PPi, AMP and ADP - Das, Priyadip; Ghosh, Amrita; Kesharwani, Manoj K.; Ramu, Vadde; Ganguly, Bishwajit; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
A new ZnII–2,2′:6′,2″-terpyridine complex, derivatized with a coumarin moiety (L1Zn), acts as a fluorescent chemosensor for different biologically important phosphates like PPi, AMP and ADP in mixed aqueous media. Depending on the proportion of the aqueous fraction present in the solvent mixture, L1Zn shows a preference for different phosphate moieties at physiological pH. In an aqueous acetonitrile (2:3, v/v) medium this reagent shows a preference for AMP as compared to ADP, ATP and PPi. The binding affinities of L1Zn with different phosphate ions and associated shifts in the electronic spectra were rationalized by DFT calculations. Such an example of a receptor that is selective for AMP under physiological conditions is rare in the literature.